1968
DOI: 10.1113/jphysiol.1968.sp008409
|View full text |Cite
|
Sign up to set email alerts
|

Renal contribution to thoracic duct lymph in dogs

Abstract: SUMMARY1. The renal contribution to thoracic duct lymph was measured in seventeen anaesthetized fasting dogs by measurement of thoracic duct flow before and after renal arterial occlusion.2. In eight experiments it was shown that thoracic duct flow and glomerular filtration rate were not significantly affected by the operation to expose the renal artery.3. In three experiments occlusion of the renal vein, after release of arterial occlusion, resulted in a sudden increase in thoracic duct flow.4. In animals inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1970
1970
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…By the same method, unilateral renal lymph flow can be estimated from the values reported here at 0.5 to 0.6 ml/hour/kg body weight. This is in close agreement with the value of 0.56 ml/hour/kg obtained by a different method in a previous study (1). In both studies the intravenous infusion rates were comparable and renal lymph flow was found to be related to body weight.…”
Section: Figuresupporting
confidence: 92%
“…By the same method, unilateral renal lymph flow can be estimated from the values reported here at 0.5 to 0.6 ml/hour/kg body weight. This is in close agreement with the value of 0.56 ml/hour/kg obtained by a different method in a previous study (1). In both studies the intravenous infusion rates were comparable and renal lymph flow was found to be related to body weight.…”
Section: Figuresupporting
confidence: 92%
“…Bull & Metaxas (1962) stripped the kidney from its surrounding tissue attachments and after placing the kidney in a basin they collected the fluid oozing from the cut lymphatics. O'Morchoe & O'Morchoe (1968) calculated renal lymph flow rates in the dog by measuring the rate of thoracic duct flow before and after ligating the renal artery. The fall in the thoracic duct flow that followed this procedure was considered to be the rate of renal lymph production.…”
Section: Introductionmentioning
confidence: 99%